Multi and interdisciplinarity between information science and computer science in the context of the semantic web - Coneglian, Caio Saraiva [UNESP]; Pomim Valentim, Marta Lígia [UNESP]; Santarem Segundo, José Eduardo [UNESP] (Universidade Federal da Paraíba, 2021)
The transformations of society impose new configurations in the way the disciplines are composed and related. In this context, multi and interdisciplinary can provide answers for the solution problems that are not solved within the classical sciences. One of these relationships resides between Information Science and Computer Science, whose interaction can bring contributions to both areas. The Semantic Web is an example of this type of interrelationship, born in Computer Science, but which has a great influence in the Information Science field. In this perspective, this research aims to analyze and discuss the interrelationships and the consequent points of multi and interdisciplinarities existing between Information Science and Computer Science within the Semantic Web. To do so, the research has a qualitative nature, in which starting from the layers of the Semantic Web we tried to identify which areas of Information Science that interact with Computer Science, in addition to identifying if such relations are multi or interdisciplinary. Thus, this work considered a classic Semantic Web structure, the layers, to identify the multi and interdisciplinary relationships existing between Information Science and Computer Science. It was possible to identify that the four main layers of the Semantic Web promote this relationship between the two areas of knowledge, and that in the two lower layers, it is verified that this interrelationship occurs, being able to be characterized as multidisciplinary, while in the upper two layers can be characterized as an interdisciplinary interrelationship.
Multi e interdisciplinaridade entre a ciência da informação e a ciência da computação no âmbito da web semântica
Keywords: Computer science; Information science; Interdisciplinarity; Multidisciplinary; Semantic web